2016
DOI: 10.1002/acp.3262
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for False Memories is Bigger than What Brewin and Andrews Suggest

Abstract: SummaryBrewin and Andrews (2016) reviewed the literature on false memory propensity for childhood events. In this commentary, we critically evaluate their basic claim that proneness to false memories of childhood experiences is more limited than has been articulated in the literature. We show that Brewin and Andrews were selective in their inclusion of false memory studies, thereby ignoring relevant research related to autobiographical false memories. Equally important, and in contrast to what Brewin and Andre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Furthermore, in general, research suggests that negative events are more likely to be misremembered than are more mundane events (e.g., Otgaar, Candel, & Merckelbach, 2008; Porter, Taylor, & ten Brinke, 2008). This finding has been explained by the fact that because emotionally negative memories contain a high level of connectivity with other memories, it is relatively easy to activate and then remember events that were not experienced but related to the experienced event (e.g., Bookbinder & Brainerd, 2016; Otgaar, Merckelbach, et al, 2017).…”
Section: The Creation Of Implanted False Memoriesmentioning
confidence: 99%
“…Furthermore, in general, research suggests that negative events are more likely to be misremembered than are more mundane events (e.g., Otgaar, Candel, & Merckelbach, 2008; Porter, Taylor, & ten Brinke, 2008). This finding has been explained by the fact that because emotionally negative memories contain a high level of connectivity with other memories, it is relatively easy to activate and then remember events that were not experienced but related to the experienced event (e.g., Bookbinder & Brainerd, 2016; Otgaar, Merckelbach, et al, 2017).…”
Section: The Creation Of Implanted False Memoriesmentioning
confidence: 99%
“…Research has shown that it is also possible, under certain circumstances, to develop false memories for entire events (e.g., Loftus and Pickrell, 1995), including criminal events (Shaw & Porter, 2015; but see also Wade, Garry, & Pezdeck, 2018;Shaw, 2018). Systematic reviews of false memory research have seen rates ranging from 15% (Brewin & Andrews, 2017; but see Otgaar, Merckelbach, Jelicic, & Smeets, 2017;Nash, Wade, Garry, Loftus, & Ost, 2017) to 30% (Scoboria et al, 2017) of participants developing false memories.…”
Section: Recovered Memory Therapy and Beliefs About Repressed Memorymentioning
confidence: 99%
“…Inspired by the recovered memory debate, a plethora of research has been conducted on the elicitation of false memories (e.g., Frenda, Nichols, & Loftus, 2011 ). Although these studies have been informative ( Otgaar, Merckelbach, Jelicic, & Smeets, 2017 ), some memory researchers have remained critical about the generalizability of their findings (e.g., Pezdek & Lam, 2007 ; but see Wade et al, 2007 ). In many of these studies, healthy participants were tested using a variety of different false memory procedures.…”
Section: Psychopathology In Practicementioning
confidence: 99%